Images of childhood in Classical Athens - Santos de Moraes, Alexandre; Lessa, Fábio de Souza (Romanitas - Revista de Estudos Grecolatinos, 2020)
In this article, we aim to ponder on the role of infancy in the Athenian society in the scope of the classical period (5th and 4th centuries B.C.). We start with the difficulty of definition and conceptualization of this age range among the Hellenes, in addition to their negative social perspective about them, in order to understand the importance of children in Athens, far beyond the perpetuation of the domestic group and of the polis. To do so, we intend to take also into account their affective relations in the family’s realm as well as their socialization by means of games and children’s play. The Attic images painted on ceramic supports will be the major type of document used in this study.